Perforation-mediated modified atmosphere packaging (PM-MAP) and shelf-life of pomegranate fruit arils (cv. ACCO) - Hussein, Zaharan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScFoodSc)--Stellenbosch University, 2014.